Parents' and children's violent gameplay: role of co-playing. Issue 6 (15th November 2018) - Walker, Doug; Brocato, E. Deanne; Carlson, Les; Laczniak, Russell N.
Abstract : Purpose: The purpose of this study is to explore the role of co-playing as a moderator of the relation between parents' and children's play of violent video games. Design/methodology/approach: The study uses dyadic parent/child survey data to estimate the conditional effects in the model, both direct and indirect. Findings: The positive effect of parents' violent video game play of children's playing behaviors is attenuated by parent/child co-playing. Parents' knowledge of the Entertainment Software Rating Board (ESRB) ratings leads to higher levels of co-playing, thereby indirectly attenuating violent video game play in children as driven by parents' play. Research limitations/implications: The paper extends the literature on consumer socialization and the impact of co-playing and identifies an antecedent for co-playing in this context. Practical implications: The paper reveals that knowledge of the self-regulatory ESRB rules plays a valuable (indirect) role in mitigating violent video game play by children through an increase in co-playing, which attenuates the positive effect of parents' play on children's play. Originality/value: The study incorporates data from both parents and children to investigate the relationship between parents and children's violent video game play while empirically investigating the uncertainty in the literature concerning the moderating impact of co-playing.